Prediction of the Relationship of Peer Group and Family Economic Education to Entrepreneurial Intention: Economic Literacy as an Mediating Variable - Sebastian, Alice; Sihombing, Sabrina O. (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Entrepreneurship is one of the main factors that can support economic growth, business opportunities, and others. However, the number of entrepreneurs in Indonesia is still lagging compared to the number of entrepreneurs in other Asian countries. Therefore, this study aims to examine the relationship between family and peer group financial education mediated by financial literacy and entrepreneurial intentions. This study uses a quantitative method where data is collected through an electronic questionnaire. There were 160 respondents in this study who were students from several universities in Jakarta and Tangerang. After checking the reliability and validity of the data, hypothesis testing was carried out using PLS-SEM. The results of the analysis show that there is one of the seven research hypotheses that are not supported. This study supports that family economic education and peer groups have a positive relationship with economic literacy. Furthermore, family economics, peer groups, and economic literacy are directly related to entrepreneurial intentions. The results of the analysis also show that economic literacy mediates the relationship between peer groups and entrepreneurial intentions. However, the results of the analysis show that economic literacy does not mediate the relationship between family economic education and entrepreneurial intention.